ANTECEDENTES PSICOLÓGICOS DE LA COMUNICACIÓN: PSYCHOLOGICAL ANTECEDENTS OF COMMUNICATION - Hechavarría Teruel, María Mercedes; Ochoa Brito, María Antonia; Zayas Leyva, Popea (Opuntia Brava, 2018)
El artículo aborda los antecedentes psicológicos de la categoría comunicación desde diferentes posiciones. Se explica la concepción de la psicología no marxista acerca de la comunicación y la concepción de los psicólogos marxistas. Se analiza el lugar que ocupa la categoría comunicación en la teoría de la personalidad. ABSTRACT This article deals with the psychological antecedents of the communication from different positions. The non-Marxist and the Marxist psychological conceptions are explained. It is analyzed the place the category communication occupies within the personality theory. KEY WORDS: Psychological support of communication, psychological conceptions of communication, theory of personality.